PENGARUH STRES KERJA DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PT MITRA DINAMIS SEJAHTERA - Mulyani, Dwi; Tampubolon, Rikson Pandapotan (LPPM Universitas Putera Batam, 2019)
Job stress and leadership problems often occur by PT Mitra Dinamis Sejahtera. It cannot be denied that work stress and leadership is one that can improve employee performance. With improved employee performance. Authors Help Know work stress, leadership, performance of employees of PT Mitra Dinamis Sejahtera. Sampling used in this study is saturated sampling, with methods of collecting data through questionnaires. The number of samples was 135 respondents who made PT Mitra Dinamis Sejahtera employees as respondents. Furthermore, the data collected in this study were analyzed by analysis that was presented in a multiple linear manner with SPSS version 20. The results of this study relate to the results of the research t, which is related to the independent variable namely work stress that is significantly generated to improve company performance, significant relationships towards improving employee performance. The F test results amounted to 246.501> from the f table of 2.672. with a significance value of 0.00 which is smaller than the value of α 0.05, it indicates that work stress variables and leadership variables together influence employee performance.